(untitled) (Transport systems and technologies, 2022)
The article examines the experimental and theoretical justification of the use of basalt fiber, as a promising material, with the help of which it is possible to obtain a new class of building materials. As a result, it was established that an increase in temperature contributes to an increase in alkali resistance of the fiber. The mass loss during aging in an alkaline solution after 28 days is about 5%, while the initial fiber loses more than 30% of the fiber mass during this time. A further increase in the temperature of isothermal aging is not effective due to a decrease in alkali resistance of the fibers and economic impracticability. To explain the processes occurring in the structure of the fiber during its heat treatment, X-ray images and spectra of the original and heat-treated fiber were obtained. In the process of heat treatment from 300 to 500 0С, the processes of defect healing, changes in the chemical composition and surface structure of the fibers occur as a result of Fe+2 → Fe+3 oxidation and the formation of iron oxide tetrahedra [FeO4]Na with the attraction of alkaline cations to the surface of the fibers. The expediency of thermal treatment of basalt fiber at a temperature of 500 0C is substantiated, which leads to compaction of the fiber structure and contributes to increasing its alkali resistance, which is confirmed by the morphostructural features of the surface of heat-treated basalt fiber aged in cement mortar.